2022
DOI: 10.1021/jacs.1c12324
|View full text |Cite
|
Sign up to set email alerts
|

Large Pressure Effects Caused by Internal Rotation in the s-cis-syn-Acrolein Stabilized Criegee Intermediate at Tropospheric Temperature and Pressure

Abstract: Criegee intermediates are important atmospheric oxidants, and quantitative kinetics for stabilized Criegee intermediates are key parameters for atmospheric modeling but are still limited. Here we report barriers and rate constants for unimolecular reactions of s-cis-syn-acrolein oxide (scsAO), in which the vinyl group makes it a prototype for Criegee intermediates produced in the ozonolysis of isoprene. We find that the MN15-L and M06-2X density functionals have CCSD­(T)/CBS accuracy for the unimolecular cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…We have investigated R4 using the dual-level rate strategy developed by our group that combines transition state theory at the W2X//DF-CCSD­(T)-F12b , /jun′-cc-pVDZ level, with variational transition state theory including small-curvature tunneling , at the M08-HX/MG3S , level. The jun′-cc-pVDZ basis set is a revision of jun-cc-pVDZ, which is similar to the jun′-cc-pVTZ basis set from jun-cc-pVTZ in our previous investigation . The pressure-dependent rate constants were calculated using the system-specific quantum Rice–Ramsperger–Kassel (SS-QRRK) theory; the validity of this method was further shown by master equation (ME) calculations in the SI (Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…We have investigated R4 using the dual-level rate strategy developed by our group that combines transition state theory at the W2X//DF-CCSD­(T)-F12b , /jun′-cc-pVDZ level, with variational transition state theory including small-curvature tunneling , at the M08-HX/MG3S , level. The jun′-cc-pVDZ basis set is a revision of jun-cc-pVDZ, which is similar to the jun′-cc-pVTZ basis set from jun-cc-pVTZ in our previous investigation . The pressure-dependent rate constants were calculated using the system-specific quantum Rice–Ramsperger–Kassel (SS-QRRK) theory; the validity of this method was further shown by master equation (ME) calculations in the SI (Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Table S3 also shows that the calculated zero-point vibrational energies are reliable at the DF-CCSD­(T)-F12b/jun′-cc-pVDZ level. However, we have noted earlier that the quantitative determination of zero-point vibrational energies for some Criegee reactions is extremely difficult . We also note that MN15-L/MG3S, M11-L/MG3S, and B3LYP/MG3S have larger MUDs at least above 0.5 kcal/mol (see Table S3).…”
Section: Resultsmentioning
confidence: 69%
“…However, we have noted earlier that the quantitative determination of zero-point vibrational energies for some Criegee reactions is extremely difficult. 108 We also note that MN15-L/MG3S, M11-L/MG3S, and B3LYP/MG3S have larger MUDs at least above 0.5 kcal/mol (see Table S3). This again reflects that it is difficult choosing a reliable functional method for obtaining quantitative zero-point vibrational energies at 0 K.…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, post-CCSD­(T) calculations are required to obtain quantitative barrier heights due to these slightly large T1 diagnostic values . However, our previous investigations have shown that post-CCSD­(T) calculations contribute to only approximately 0.5 kcal/mol. Additionally, computational costs are prohibitive for post-CCSD­(T) calculations for the reaction systems investigated here. Therefore, we ignore the post-CCSD­(T) calculations in this work.…”
Section: Computational Methodsmentioning
confidence: 93%